2011
DOI: 10.1017/s002185961100058x
|View full text |Cite
|
Sign up to set email alerts
|

Uniculm and conventional tillering barley accessions under northern growing conditions

Abstract: At high northern latitudes, growing seasons are short with long days. In these conditions, tillering is an unwanted trait in barley (Hordeum vulgare L.), because the grains on tillers develop later than those on the main stem and are often harvested before they are fully mature, leading to reductions in overall quality. Hence, the uniculm growth habit has been considered an interesting option for boreal barley production. The aim of the present study was to determine the differences in the yield formation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, after the restoration of watering, plants are capable of accelerated production of new tillers in order to compensate for a loss in biomass caused by stress, but newly formed tillers usually generate a lower yield. The negative effects of drought on grain yield were confirmed by numerous reports, which indicated that water deficit occurring at tillering, heading and grain filling stages caused the greatest loss in yield (Sakamoto and Matsuoka 2004; Blum 2005; Khomari et al 2008; Mäkelä and Muurinen 2011). …”
Section: Discussionmentioning
confidence: 63%
“…However, after the restoration of watering, plants are capable of accelerated production of new tillers in order to compensate for a loss in biomass caused by stress, but newly formed tillers usually generate a lower yield. The negative effects of drought on grain yield were confirmed by numerous reports, which indicated that water deficit occurring at tillering, heading and grain filling stages caused the greatest loss in yield (Sakamoto and Matsuoka 2004; Blum 2005; Khomari et al 2008; Mäkelä and Muurinen 2011). …”
Section: Discussionmentioning
confidence: 63%
“…Subsequently, carbohydrate partitioning during grain filling is greater to the main stem than to tillers ( Hay 1995 , Peltonen-Sainio et al 2008 ). As a result, the tertiary tillers are aborted due to an insufficient amount of carbohydrates at anthesis ( Sakamoto and Matsuoka 2004 , Gonzalez et al 2011 , Mäkelä and Muurinen 2011 ), which leads to reduced grain yield in tillers, but could contribute to increased weight in the primary stem.…”
Section: Discussionmentioning
confidence: 99%
“…Tiller number is a key component of barley grain yield (Sakamoto and Matsuoka 2004). Fertile tillers contribute significantly to grain yield improvement, but those tillers without fertile spikes decrease the harvest index (Mäkelä and Muurinen 2011). In our study we noticed an increase in the number of productive tillers triggered by drought conditions which could be explained by the secondary tiller development process, commonly observed in the field conditions (Aspinall et al 1964).…”
Section: Discussionmentioning
confidence: 99%